Entrepreneurial Competence and Small and medium enterprises' Profitability: A Case of sunflower oil processing enterprises in Tanzania - Rabisante Moshi; Salum Matotola (Cogent Business & Management, 2023)
Determine the influence of entrepreneurial competence on SMEs' profitability focusing on personal, interpersonal and business competencies on SMEs' profitability. A cross-sectional research design whereby data were collected at once from 102 randomly selected sunflower oil processing firms in Dodoma region in Tanzania. Structured questionnaires were used to collect data. The study's findings reveal that personal, interpersonal and business competencies had a positive significant influence on the profitability of SMEs (p<0.05). Integration of personal, interpersonal, and business competence influences profitability of sunflower processing firms. Involvements of personal, interpersonal, and business competencies influence the profitability of SMEs (sunflower processing firms).
Keywords: 650; Competencies; Entrepreneurship; Processing; Profitability; SMEs; Sunflower